Improving the utilization of implantable cardioverter defibrillators for sudden cardiac arrest prevention (Improve SCA) in developing countries: Clinical characteristics and reasons for implantation refusal. Issue 12 (31st October 2018) - Singh, Balbir; Zhang, Shu; Ching, Chi‐Keong; Huang, Dejia; Liu, Yen‐Bin; Rodriguez, Diego A.; Hussin, Azlan; Kim, Young‐Hoon; Chasnoits, Alexandr Robertovich; Cerkvenik, Jeffrey; Muckala, Katy A.; Cheng, Alan
Abstract: Background: Despite available evidence that implantable cardioverter defibrillators (ICDs) reduce all‐cause mortality among patients at risk for sudden cardiac death, utilization of ICDs is low especially in developing countries. Objective: To summarize reasons for ICD or cardiac resynchronization therapy defibrillator implant refusal by patients at risk for sudden cardiac arrest (Improve SCA) in developing countries. Methods: Primary prevention (PP) and secondary prevention (SP) patients from countries where ICD use is low were enrolled. PP patients with additional risk factors (syncope, ejection fraction < 25%, nonsustained ventricular tachycardia [NSVT], or frequent premature ventricular complexes) were further categorized as "1.5 PP patients." Candidates who declined implantation were asked for reasons for refusal. Baseline factors that may have influenced the implant decision were examined using logistic regression. Results: Among 3892 patients, the implant refusal rate was 46.5% among PP patients ( n = 2700), and 10.3% among SP patients ( n = 1192). The most common refusal reason was inability to pay for the device (53.8%), followed by not believing in the benefits of the ICD (19.4%). Among PP ICD candidates, those with no syncope, no NSVT, no premature ventricular contractions, shorter QRS duration, no atrial arrhythmias, and no left bundle branch block were more likely to refuse implant. Among SP candidates, a history of cardiovascular surgery and no sinus node dysfunction were significant predictors of ICD refusal. Additionally, countries had significant differences in patient refusal rates among PP and SP groups. Conclusion: Implant refusal among PP patients is high in many countries. Increased reimbursement and better awareness of the benefits of an ICD could increase their utilization.